2022
DOI: 10.3390/nu14101995
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Community Nutrition Environment, Food and Drink Purchases and Consumption on Journeys between Home and School: A Wearable Camera Study

Abstract: Children’s community nutrition environments are an important contributor to childhood obesity rates worldwide. This study aimed to measure the type of food outlets on children’s journeys to or from school, children’s food purchasing and consumption, and to determine differences by ethnicity and socioeconomic status. In this New Zealand study, we analysed photographic images of the journey to or from school from a sample of 147 children aged 11–13 years who wore an Autographer camera which recorded images every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Australian children are exposed to high levels of outdoor advertising for unhealthy food and drink on school routes, 32 with exposure to unhealthy food advertising known to encourage a preference for and purchasing of unhealthy foods by children 33 . International studies have found that among adolescents, active travel is associated with an increased likelihood of consumption of fast food compared to car travel, related to higher fast‐food purchasing opportunities 34 , 35 . Secondary students with pocket money are more likely to consume fast food (overall) than those with no pocket money 36 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Australian children are exposed to high levels of outdoor advertising for unhealthy food and drink on school routes, 32 with exposure to unhealthy food advertising known to encourage a preference for and purchasing of unhealthy foods by children 33 . International studies have found that among adolescents, active travel is associated with an increased likelihood of consumption of fast food compared to car travel, related to higher fast‐food purchasing opportunities 34 , 35 . Secondary students with pocket money are more likely to consume fast food (overall) than those with no pocket money 36 .…”
Section: Discussionmentioning
confidence: 99%
“…33 International studies have found that among adolescents, active travel is associated with an increased likelihood of consumption of fast food compared to car travel, related to higher fast-food purchasing opportunities. 34,35 Secondary students with pocket money are more likely to consume fast food (overall) than those with no pocket money. 36 Interventions to increase active travel should also mitigate the potential unintended consequences related to increased exposure to unhealthy food marketing and environments along the school journey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…explore the relationship between the food environment, purchasing patterns, and dietary behavior. These studies underscore the importance of considering geographic and economic factors when designing interventions to improve access to healthy foods [5][6][7][8][9]. In particular, Salvo et al highlight the potential impact of policies that jointly increase geographic and economic access to fruit and vegetables among low-income, predominantly Latino urban residents [9].…”
mentioning
confidence: 99%